A qualitative examination on the implementation of participatory “A”rt-based activity on “Health” of older community-dwellers: what worked for the Singapore A-Health Intervention? - Ma, Stephanie Hilary Xinyi; Tan, Michael Koon Boon; Goh, Shannon Shuet Ning; Yeo, Gabriellia; Teng, Alicia; Yang, Yilin; Galéry, Kévin; Beauchet, Olivier; Ho, Andy Hau Yan (Frontiers in Medicine, 2023)
Introduction Art and museum-based interventions are gaining increasing recognition for their potential as low-risk activities for older adults, offering numerous physical, cognitive, and emotional benefits. However, there remains a dearth of knowledge regarding the science of implementation as well as the factors and processes that contribute to their effectiveness from the perspectives of intervention participants. Methods The current research draws on the qualitative evaluation data obtained from a larger mixed-method randomized control trial that evaluated a standardized Participatory “A”rt-Based Activity On “Health” of Older Community-Dwellers—the Singapore A-Health Intervention. Adopting a participatory action research approach, the primary objective is to critically examine the lived experiences and health impact of the Singapore A-Health Intervention with a secondary objective to uncover strategies for optimized implementation outcomes. All 56 participants who completed the intervention filled out a program evaluation survey and a nested sample of 30 participants completed a series of acceptability focus groups. Results Descriptive analyses of the program evaluation survey data revealed that 96.2% of participants were satisfied with the overall experience of the Singapore A-Health intervention (M = 9.00, SD = 1.76), reported that the intervention positively impacted their quality of life (M = 8.90, SD = 1.43), and social wellbeing (M = 8.92, SD = 1.43). Thematic analysis with a grounded theory approach on the qualitative focus group data revealed three interrelated themes detailing how the Singapore A-Health Intervention contributed to positive health and wellbeing outcomes (1. A-Health Experience, 2. Wellbeing Outcomes, 3. Enabling Factors) and nine subthemes (1a. Intellectual Stimulation, 1b. Positive Stress, 1c. Peer Interaction, 2a. Interpersonal Bonds, 2b. Personal Growth, 2c. Mindful Living, 3a. Integrated Support, 3b. Session Design, 3c. Mode of Engagement). Discussion This investigation provides important insights to the Singapore A-Health intervention’s effectiveness for enhancing wellbeing among older adults, as well as the factors that enable successful program implementation. These findings offer a culturally unique perspective on the benefits of art and museum interventions, while underscoring the imperative need for strong partnership and collaborations among community stakeholders in supporting the health and wellbeing of ageing populations.